“Apenas encaminhado”: categorizações como estratégias discursivas de (in)efetivação de garantias fundamentais em uma decisão do Supremo Tribunal Federal - Padua, João Pedro (Language and Law / Linguagem e Direito, 2017)
As demonstrated by the recent decision of a Federal Judge to coercively bring former President Lula da Silva to give a testimony before the Federal Police, judicial decisions can bring about a big controversy in the legal community, even when the normative parameters for deciding are considered uncontroverted. This paper investigates the discursive strategies for constructing the basis for judicial decision, with a focus on one decision by the (Brazilian) Supreme Federal Court, which served as precedent for decisions such as that in the former President case. Using as an analytical tool the concept of Membership Categorization Devices, originally created by Harvey Sacks, this paper spots how the discursive creation of these devices legitimates strategies for meaning negotiation of legal norms in – and for – the specific case to be decided. Implications of the analysis for other cases and cross-referencing of this data with that of other studies in judicial decisions in Brazil are discussed.